UJI TAK MERUSAK SHORT PIN PWR – FUEL DUMMY PASCA IRADIASI - Sigit, Rohmad; Artika, Refa; Ajiriyanto, Maman Kartaman; Yulianto, Tri (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
NON-DESTRUCTIVE TEST OF IRRADIATED SHORT PIN OF PWR TYPE – FUEL DUMMY. Post- irradiation examination (PIE) for nuclear fuel is used as an indicator of fuel performance reliability during the irradiation process. The Center for Nuclear Fuel Technology (PTBBN) conducts research and development of nuclear fuel for Pressurized Water Reactor (PWR). Short pin of PWR fuel dummy with zircaloy-4 cladding has been irradiated at the Multipurpose Reactor – G.A. Siwabessy (RSG-GAS) and has been sent to the Radiometallurgy Installation (IRM) – PTBBN. Non-destructive tests conducted at the IRM includes visual observation and X-ray radiographic test. Visual observations using a digital camera were done in hot cell 102, while X-ray radiographic test was carried out in hot cell 103 IRM. X-ray radiographic test using the voltage and current parameters at a range of 120-125 kV and 1000-1100 uA. The test material was placed at a height of 60 cm from the detector to obtain a 100% magnification. Visual observation shows the formation of several spots indicating oxidation on the short pin PWR fuel dummy surface. Radiographic images from X- ray radiographic testing do not show any anomalies, which is indicated by relatively homogeneous gray value in the axial and radial directions. Generally, based on the non-destructive test results, performance of the short pin PWR - fuel dummy is relatively satisfactory with no significant defects. To confirm the existence of oxides formation on the surface of the short pin PWR fuel dummy, Eddy Current test is needed, followed by microstructure observations.